Gender Discrimination in Family Matters, Albanian Legal Framework - Advisor, Drita Shkurti-Legal Advisor; Cipa, Adrian; Cukaj, Lirime (Journal of Cultural Analysis and Social Change, 2025)
The Albanian society, as well as the international community, has evolved over the years towards democratic values, which are fundamentally based on the respect and guarantee of human rights and freedoms. This paper focuses on the treatment of several key aspects of equality in matters related to family relationships, from which elements can be concluded that may be considered discriminatory in the context of gender stereotypes. Recognizing that family relationships are complex and the subject is very broad, we have endeavored to focus on issues that can be considered problematic for Albanian society in particular and the world in general. Here, we mention issues such as domestic violence, aspects of equality in matters pertaining to marriage, and relationships within the exercise of parental responsibility. Despite the progress made towards the establishment of an equal world, we observe that there are still aspects that need improvement in this regard, both in terms of legal frameworks and in the implementation of laws. This article aims to provide an approach to these issues, though it does not exhaustively analyze the subject matter.